Non-eosinophilic esophagitis eosinophilic gastrointestinal diseases are more prevalent than eosinophilic esophagitis in Korean children: from a multicenter study based on new diagnostic criteria and nomenclature - Lee, Kunsong; Kang, Ben; Kim, Eun Sil; Yi, Dae Yong; Kim, Tae Hyeong; Lee, Yoo Min; Choi, Sujin; Choe, Byung-Ho (Frontiers in Pediatrics, 2025)
BackgroundEosinophilic gastrointestinal diseases (EGIDs) are chronic inflammatory disorders characterized by eosinophilic infiltration of the gastrointestinal (GI) tract. This study aimed to investigate the epidemiological and clinical characteristics of pediatric EGIDs in Korea based on the newly established nomenclature and diagnostic guidelines.MethodsA retrospective analysis was conducted on pediatric patients (0–18 years) with GI symptoms who underwent upper and lower GI endoscopy at five tertiary hospitals in Korea (2010∼2023). Patients were classified based on the latest diagnostic criteria into eosinophilic esophagitis (EoE) and non-eosinophilic esophagitis eosinophilic gastrointestinal disease (non-EoE EGIDs), including eosinophilic gastritis (EoG), eosinophilic enteritis (EoN), and eosinophilic colitis (EoC). Clinical, laboratory, and endoscopic findings were analyzed.ResultsAmong a total of 4,972 pediatric endoscopic procedures (3,300 upper and 1,672 lower), 63 cases (1.3%) of EGIDs were diagnosed, with non-EoE EGIDs (65.1%) being more prevalent than EoE (34.9%). Within the non-EoE EGIDs group, EoG was the most common subtype (33.3%), followed by EoN (20.6%) and EoC (7.9%). Multi-site involvement was observed in 30.2% with frequent esophageal involvement (EI). Endoscopic abnormalities, including rings and furrows in EoE and ulcers in non-EoE EGIDs, were common. Peripheral eosinophil counts and fecal calprotectin levels were significantly higher in non-EoE EGIDs with EI than in EoE (P < 0.05). The relapse rates exceeded 20% across all subtypes.ConclusionThis study highlights the distinctive epidemiology of pediatric EGIDs in Korea, where non-EoE EGIDs are more prevalent than EoE, contrasting with Western reports. Peripheral eosinophil counts and fecal calprotectin levels were significantly higher in non-EoE EGIDs with EI than in EoE.